Switching device

The switch device addresses the limitations of existing switch devices by using a tempered glass layer with a specific thickness for enhanced scratch resistance, cleaning, texture, and strength, while ensuring effective contact switching.

JP7651061B2Active Publication Date: 2025-03-25NITTO DENKO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024503272
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-02-28
Filing Date
2023-02-24
Publication Date
2025-03-25
Estimated Expiration
2043-02-24

AI Technical Summary

Technical Problem

Existing switch devices with movable contacts made of flexible resin suffer from scratch resistance issues, difficulty in cleaning with solvents, poor texture, and insufficient strength.

Method used

A switch device featuring a tempered glass layer with a thickness of 100 μm to 200 μm, which is elastically deformed to switch contacts between conduction and non-conduction, while the switch section is mounted on the backside of the glass layer.

Benefits of technology

The solution enhances scratch resistance, solvent cleaning ability, texture, and provides sufficient strength to the switch device, while maintaining the ability to switch contacts effectively.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651061000001
    Figure 0007651061000001
  • Figure 0007651061000002
    Figure 0007651061000002
  • Figure 0007651061000003
    Figure 0007651061000003
Patent Text Reader

Abstract

This switch device is provided with: a glass layer comprising tempered glass; and a switch unit disposed on the back surface side of the glass layer. The thickness of the glass layer is 100 μm to 200 μm, inclusive. The switch unit is provided with a plurality of contacts including a contact that is movable in the vertical direction. When the glass layer is pressed, the glass layer elastically deforms so as to switch between conduction and non-conduction of the plurality of contacts.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a switch device. [Background technology]

[0002] Switches that mechanically control electrical contact are widely used as an input method for electronic components. One such switch is the tactile switch shown in Patent Document 1. This type of switch has a sliding button that can self-recognize on / off, and is therefore considered to have the advantage of being less prone to malfunction than touch-type switches.

[0003] Among these types of switches, switches that have contacts that can move up and down and slide up and down use a flexible and unbreakable resin for the outermost surface. However, the surface of resin is easily deteriorated by scratches, is difficult to clean with solvents, has a poor texture, and is not strong enough. Therefore, a switch device that solves these problems is required. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 06-203679 Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in consideration of the above points, and aims to provide a switch device having contacts that can move up and down, which has improved scratch resistance, solvent cleanability, and texture, while also having sufficient strength. [Means for solving the problem]

[0006] This switch device has a glass layer made of tempered glass and a switch unit arranged on the back side of the glass layer, the thickness of the glass layer being between 100 μm and 200 μm, the switch unit having a plurality of contacts including a contact that can move up and down, and when the glass layer is pressed, the glass layer elastically deforms, switching between conductive and non-conductive states of the plurality of contacts. Effect of the Invention

[0007] According to the disclosed technology, in a switch device having contacts that can move up and down, it is possible to improve scratch resistance, solvent cleanability, and texture, while also providing sufficient strength. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a cross-sectional view (part 1) illustrating a switch device according to a first embodiment. [Diagram 2] 2 is a plan view illustrating a frame of the switch device according to the first embodiment. FIG. [Diagram 3] FIG. 4 is a second cross-sectional view illustrating the switch device according to the first embodiment. [Figure 4] FIG. 2 is a diagram showing conditions and results of an example and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In the drawings, the same components are designated by the same reference numerals, and duplicated explanations may be omitted.

[0010] Fig. 1 is a cross-sectional view (part 1) illustrating a switch device according to a first embodiment. As shown in Fig. 1, the switch device 1 has a support portion 10, a bonding layer 20, a frame 30, a bonding layer 40, a resin layer 50, a bonding layer 60, a glass layer 70, and a switch portion 80. Note that the support portion 10, the frame 30, the bonding layer 40, the resin layer 50, and the bonding layer 60 are not essential components of the switch device 1.

[0011] One surface 70a of the glass layer 70 becomes the outermost surface of the switch device 1. Other members such as the support portion 10 and other layers are disposed on the other surface 70b (rear surface side) of the glass layer 70. The switch device 1 is mounted on, for example, a wiring board.

[0012] Here, the materials and the like of each part of the switch device 1 will be described.

[0013] [Support part] The support section 10 is disposed on the other surface 70b side (rear surface side) of the glass layer 70, and supports the glass layer 70 and the like. The support section 10 can be disposed, for example, outside the switch section 80 in a frame shape so as to surround the switch section 80. Alternatively, a plurality of support sections 10 may be disposed at intervals at any positions outside the switch section 80. The support section 10 is formed, for example, from a resin, a metal, or the like.

[0014] Note that a component constituting the switch section 80 may be used as the support section. Alternatively, the switch section 80 itself may be used as the support section. That is, the support section may be a part of the switch section 80 or the whole of the switch section 80. In these cases, the support section 10 shown in FIG. 1 does not need to be provided. Alternatively, a part or the whole of the switch section 80 may be used as the support section, and the support section 10 shown in FIG. 1 may be provided separately from the switch section 80.

[0015] [Joining layer] Any adhesive or bonding agent can be used as the bonding layers 20, 40, and 60. In this specification, an adhesive refers to a layer that has adhesive properties at room temperature and adheres to an adherend with light pressure. Therefore, even when an adherend attached to the adhesive is peeled off, the adhesive retains practical adhesive strength. On the other hand, an adhesive refers to a layer that can bond substances by being interposed between substances. Therefore, when an adherend attached to the adhesive is peeled off, the adhesive does not have practical adhesive strength.

[0016] Examples of the adhesive include adhesives having, as a base polymer, an acrylic polymer, a silicone polymer, a polyester, a polyurethane, a polyamide, a polyether, a fluorine-based polymer, a rubber-based polymer, or the like.

[0017] Examples of adhesives include polyester adhesives, polyurethane adhesives, polyvinyl alcohol adhesives, and epoxy adhesives. When the adhesive is a thermosetting adhesive, it can be heated to harden (solidify) and exert its peel resistance. When the adhesive is a photocurable adhesive such as an ultraviolet-curable adhesive, it can be hardened by irradiating it with ultraviolet light or other light and exert its peel resistance. When the adhesive is a moisture-curable adhesive, it can be hardened by reacting with moisture in the air, and can be hardened by being left to stand and exert its peel resistance.

[0018] From the viewpoint of strength, it is preferable to use an adhesive or a pressure-sensitive adhesive as the bonding layer 20, an adhesive as the bonding layer 40, and an adhesive as the bonding layer 60. The thickness of the bonding layer 20 is preferably within 5 μm to 2 mm. In view of the manufacturing method of the adhesive layer, the thickness of the bonding layer 40 is preferably 5 μm to 200 μm, more preferably 20 μm to 150 μm, and even more preferably 20 μm to 100 μm. The thickness of the bonding layer 60 is preferably 0.5 μm to 25 μm, more preferably 0.5 μm to 5 μm, and even more preferably 0.5 μm to 3 μm.

[0019] Frame The frame 30 can be interposed between the glass layer 70 and the switch section 80. In the example of FIG. 1, the frame 30 is bonded onto the support section 10 via the bonding layer 20. FIG. 2 is a plan view illustrating the frame. As shown in FIG. 2, the frame 30 has a fixed section 31 and a movable section 32 supported by an elastic support section 33 with respect to the fixed section 31. The fixed section 31 has an opening, and the movable section 32 is disposed within the opening. The fixed section 31 and the movable section 32 are supported by a plurality of elastic support sections 33 so as to be freely movable. Note that only the fixed section 31 is bonded to the support section 10, and the movable section 32 and the elastic support section 33 are not bonded to the support section 10.

[0020] In the example of FIG. 2, a circular opening is formed in the approximate center of a rectangular fixed part 31, and a circular movable part 32 is disposed within the opening. The diameter of the movable part 32 can be, for example, about 10 mm to 30 mm. In addition, in the example of FIG. 2, three elastic support parts 33 are disposed at positions that divide the circumferential direction of the movable part 32 into approximately three equal parts. However, the shapes of the fixed part 31 and the movable part 32, and the number and connection positions of the elastic support parts 33 are not limited to the example of FIG. 2. The elastic support part 33 is, for example, a spring. The spring may be a leaf spring or a coil spring. The elastic support part 33 may be a member other than a spring, such as rubber.

[0021] The frame 30 can be integrally formed from, for example, resin or metal. When the frame 30 is made of resin, materials such as ABS resin, vinyl chloride resin, polypropylene resin, polycarbonate resin, polystyrene resin, etc. can be used. When the frame 30 is made of metal, materials such as aluminum and SUS can be used. The thickness of the frame 30 can be, for example, 0.5 mm or more and 5 mm or less.

[0022] [Resin layer] The resin layer 50 can be interposed between the glass layer 70 and the switch section 80. In the example of FIG. 1, the resin layer 50 is bonded onto the fixing section 31 of the frame 30 via the bonding layer 40. The resin layer 50 has flexibility. The thickness of the resin layer 50 is preferably 50 μm or more and 150 μm from the viewpoint of flexibility. Examples of materials for the resin layer 50 include polyester resins such as polyethylene terephthalate resins and polyethylene naphthalate resins, cycloolefin resins such as norbornene resins, polyethersulfone resins, polycarbonate resins, acrylic resins, polyolefin resins, polyimide resins, polyamide resins, polyimideamide resins, polyarylate resins, polysulfone resins, polyetherimide resins, and urethane resins.

[0023] In this way, by laminating the resin layer 50 under the glass layer 70, the resin layer 50 has the effect of suppressing excessive deformation of the glass layer 70 and suppressing cracking of the glass layer 70, and at the same time, since an appropriate amount of deformation is realized, it is possible to improve the durability of the glass layer 70 when it is repeatedly elastically deformed. Note that the amount of deformation of the glass layer 70 can be controlled by changing the thickness of the resin layer 50.

[0024] A plurality of resin layers may be laminated via a bonding layer below the glass layer 70. Such a laminated structure can further suppress cracking of the glass layer 70 and can further improve the durability of the glass layer 70 when it is repeatedly elastically deformed.

[0025] [Glass layer] The glass layer 70 is laminated on the resin layer 50 via the bonding layer 60. The glass layer 70 is made of tempered glass. The tempered glass may be chemically tempered glass or thermally tempered glass, but chemically tempered glass having a compressive stress layer is easier to manufacture than thermally tempered glass. The glass layer 70 preferably has a compressive stress of 600 MPa or more.

[0026] Chemical strengthening refers to replacing ions near the surface of a glass sheet with ions with a larger ionic radius. The ion exchange forms a compressive stress layer on the surface of the glass sheet, resulting in chemically strengthened glass. The glass composition in the compressive stress layer is different from the glass composition inside the glass.

[0027] In the chemically strengthened glass, the glass plate before strengthening can be, for example, soda-lime glass, aluminosilicate glass, borosilicate glass, aluminoborosilicate glass, etc. In that the depth of the compressive stress layer does not become too large more than necessary, soda-lime glass or soda-silicate glass is preferable, and soda-lime glass is more preferable.

[0028] Ion exchange can be carried out, for example, by substituting Li ions on the surface of the glass sheet with Na ions and / or K ions. Alternatively, Na ions on the surface of the glass sheet may be substituting K ions. By such ion exchange, a compressive stress layer is formed on the surface of the glass sheet.

[0029] When Na ions are replaced with K ions, for example, a glass plate containing sodium may be brought into contact with an inorganic molten salt containing potassium nitrate. The inorganic molten salt containing potassium nitrate preferably contains at least one salt selected from the group consisting of K2CO3, Na2CO3, KHCO3, NaHCO3, KOH, and NaOH.

[0030] Considering the strength and durability required for the glass layer in the switch device, the thickness of the glass layer 70 is preferably 100 μm or more. On the other hand, the glass layer used in the switch device needs to be elastically deformable, and in consideration of sufficient elastic deformation, the thickness of the glass layer 70 is preferably 200 μm or less.

[0031] A functional layer such as an antifouling layer, an antireflection layer, a conductive layer, a reflective layer, a decorative layer, etc. may be provided on the front and / or back surface of the glass layer 70. In the switch device according to this embodiment, the glass layer 70 is located on the outermost surface. Here, "the glass layer 70 is located on the outermost surface" means that the glass layer 70 is substantially located on the outermost surface, and even if an additional layer such as the above is provided, in this embodiment, it is expressed that the glass layer 70 is located on the outermost surface.

[0032] [Switch section] The switch section 80 is disposed on the back surface side of the glass layer 70. In the example of Fig. 1, the switch section 80 is disposed inside the support section 10, and on the opposite side of the frame 30 to the glass layer 70 and the like.

[0033] Moreover, the switch section 80 has a plurality of contacts including a contact that is movable up and down. In the example of Fig. 1, the switch section 80 is a tactile switch, and has a housing 81, a film 82, a frame 83, a stem 84, a first contact 85, and a second contact 86. Of the first contact 85 and the second contact 86, the second contact 86 is a contact that is movable up and down.

[0034] The housing 81 and the frame 83 are each square-shaped and are disposed opposite each other with an adhesive film 82 sandwiched therebetween. The film 82 is disposed, for example, so as to cover the opening of the housing 81. The stem 84 is held by the frame 83 in a state in which it can slide freely in the up and down directions.

[0035] A first contact 85 and a second contact 86 are disposed on the bottom surface of the housing 81. The second contact 86 is disposed above the first contact 85 and spaced apart from the first contact 85. The film 82 and the second contact 86 are configured to be elastically deformable. The housing 81, the film 82, the frame 83, and the stem 84 are made of, for example, resin.

[0036] 1, external connection terminals electrically connected to the first contact 85 and the second contact 86 are omitted from the illustration. There is a gap of about 0.1 mm to 0.2 mm between the upper surface of the stem 84 of the switch section 80 and the lower surface of the movable section 32 of the frame 30. Note that the switch section 80 is not limited to a tactile switch, and may be a membrane switch or the like.

[0037] FIG. 3 is a cross-sectional view (part 2) illustrating the switch device according to the first embodiment, showing a state in which one surface 70a of the glass layer 70 is pressed in the direction of the arrow.

[0038] As described above, the thickness of the glass layer 70 is preferably 100 μm or more and 200 μm or less. By making the glass layer 70 have such a thickness, the glass layer 70 can be elastically deformed and can be locally recessed. When one surface 70a side of the glass layer 70 is pressed, the glass layer 70 elastically deforms together with the resin layer 50 and the bonding layer 60 to move the movable part 32 of the frame 30, and the first contact 85 and the second contact 86 of the switch part 80 are switched between contact (conduction) and non-contact (non-conduction). The glass layer 70 can be elastically deformed so as to sink, for example, about 0.5 mm to 2 mm in the vertical direction.

[0039] In the example of Fig. 1, when the glass layer 70 is not pressed, the first contact 85 and the second contact 86 of the switch unit 80 are not in contact (non-conductive state). Therefore, as shown in Fig. 3, when the glass layer 70 is pressed and deformed, the stem 84 of the switch unit 80 is pressed accordingly, and the film 82 and the second contact 86 are elastically deformed, so that the second contact 86 approaches the first contact 85, and the first contact 85 and the second contact 86 come into contact with each other and become conductive. When the force pressing the glass layer 70 is removed, the glass layer 70 returns to the state of Fig. 1, and the first contact 85 and the second contact 86 are again not in contact with each other.

[0040] In this way, by setting the thickness of the glass layer 70 to be 100 μm or more and 200 μm or less, the glass layer 70 becomes elastically deformable. As a result, when the glass layer 70 is pressed, the contacts of the switch unit 80 slide up and down in accordance with the local deformation of the glass layer 70, and the multiple contacts of the switch unit 80 can be switched between conductive and non-conductive states.

[0041] Since the outermost surface of the switch device 1 is the glass layer 70, it is possible to improve scratch resistance, solvent cleanability, and texture compared to a case where the outermost surface is made of resin. Also, since the glass layer 70 of the switch device 1 is made of tempered glass, it is possible to provide sufficient strength and durability compared to a case where the glass layer 70 is made of untempered glass. Also, since the switch device 1 is a sliding type switch, it is possible to obtain a tactile sensation when pressed and to reduce the risk of malfunction.

[0042] Although a type that uses capacitance or the like can be considered as a switch that uses glass on the top surface, it is difficult to create an up-and-down sliding action with ordinary plate glass. Therefore, there is no tactile sensation when pressed, and there is a risk of malfunctioning even if touched unintentionally.

[0043] [Example 1] In Example 1, a switch device having the structure shown in Fig. 1 was produced. Chemically strengthened glass with a compressive stress of 600 MPa was used as the glass layer 70, and the thickness was set to 200 µm. PET was used as the material for the resin layer 50, and the thickness was set to 100 µm. The bonding layer 60 was an adhesive, and epoxy resin was used as the material, and the thickness was set to 1 µm.

[0044] [Example 2] In Example 2, a chemically strengthened glass having a compressive stress of 600 MPa and a thickness of 150 μm was used as the glass layer 70. A switch device was produced in the same manner as in Example 1 except for the above.

[0045] [Example 3] In Example 2, a chemically strengthened glass having a compressive stress of 600 MPa and a thickness of 100 μm was used as the glass layer 70. A switch device was produced in the same manner as in Example 1 except for the above.

[0046] [Comparative Example 1] In Comparative Example 1, a chemically strengthened glass having a compressive stress of 600 MPa and a thickness of 300 μm was used as the glass layer 70. A switch device was produced in the same manner as in Example 1 except for the above.

[0047] [Comparative Example 2] In Comparative Example 2, a chemically strengthened glass having a compressive stress of 600 MPa and a thickness of 50 μm was used as the glass layer 70. A switch device was produced in the same manner as in Example 1 except for the above.

[0048] [Comparative Example 3] In Comparative Example 3, unstrengthened glass was used as the glass layer 70, and the thickness was set to 200 μm. A switch device was produced in the same manner as in Example 1 except for the above.

[0049] [Comparative Example 4] In Comparative Example 4, unstrengthened glass was used as the glass layer 70, and the thickness was set to 100 μm. A switch device was produced in the same manner as in Example 1 except for the above.

[0050] [Rating 1] For the switch devices produced in Examples 1 to 3 and Comparative Examples 1 to 4, it was confirmed whether or not the glass layer 70 would elastically deform when pressed, thereby pressing the switch portion 80. Specifically, it was confirmed whether or not the switch portion 80 would switch from non-conductive to conductive when pressed with a load of 5 N from the glass layer 70 side in the direction of the arrow in Fig. 3, and a mark of ◯ was used if the switch portion switched, and a mark of × was used if the switch portion did not switch.

[0051] [Rating 2] A strength test was performed on the switch devices produced in Examples 1 to 3 and Comparative Examples 1 to 4 to visually check whether cracks occurred in the glass layer 70. If no cracks were observed, they were marked with a circle, and if cracks were observed, they were marked with a cross. The strength test was performed in accordance with the spring hammer test specified in JIS C4526-1:2021. The force applied to the switch device in the spring hammer test was 0.5 J.

[0052] [Evaluation Results] The evaluation results are shown in Fig. 4. From Examples 1 to 3 in Fig. 4, it was confirmed that by using chemically strengthened glass with a compressive stress of 600 MPa as glass layer 70 and setting the thickness to 100 µm to 200 µm, it is possible to switch the conduction and non-conduction of the switch portion and to obtain sufficient strength.

[0053] In contrast, Comparative Example 1 confirmed that even if chemically strengthened glass having a compressive stress of 600 MPa is used as the glass layer 70, if the thickness is 300 μm, the strength is too high to elastically deform, and the switch section cannot be switched between conductive and non-conductive. Also, Comparative Example 2 confirmed that even if chemically strengthened glass having a compressive stress of 600 MPa is used as the glass layer 70, if the thickness is 50 μm, sufficient strength cannot be obtained. Also, Comparative Examples 3 and 4 confirmed that if unstrengthened glass is used as the glass layer 70, sufficient strength cannot be obtained even if the thickness is 100 μm or 200 μm.

[0054] Although preferred embodiments have been described above in detail, the present invention is not limited to the above-described embodiments, and various modifications and substitutions can be made to the above-described embodiments without departing from the scope of the claims.

[0055] This international application claims priority based on Japanese Patent Application No. 2022-029745, filed on February 28, 2022, and the entire contents of Japanese Patent Application No. 2022-029745 are incorporated by reference into this international application. [Explanation of symbols]

[0056] 1 Switching device 10 Support part 20,40,60 bonding layer 30 frames 31 Fixed part 32 Moving parts 33 Elastic support part 50 Resin layer 70 Glass Layer 70a One side 70b The other side 80 Switch section 81 Housing 82 Film 83 Frames 84 Stem 85 First Contact 86 Second Contact

Claims

1. A glass layer made of tempered glass; A switch portion disposed on the rear surface side of the glass layer, The thickness of the glass layer is 100 μm or more and 200 μm or less, The switch unit includes a plurality of contacts including a contact that can move up and down, When the glass layer is pressed, the glass layer elastically deforms, switching between conductive and non-conductive states of the plurality of contacts.

2. The switch device according to claim 1 , wherein the glass layer is a chemically strengthened glass having a compressive stress layer.

3. The switch device according to claim 2 , wherein the glass layer has a compressive stress of 600 MPa or more.

4. a frame is interposed between the glass layer and the switch portion, The frame has a fixed portion and a movable portion supported by an elastic support portion relative to the fixed portion, 4. The switch device according to claim 1, wherein when the glass layer is pressed, the glass layer is elastically deformed to move the movable portion, and the plurality of contacts are switched between conductive and non-conductive states.

5. The switch device according to claim 1 , further comprising a support portion for supporting the glass layer on a rear surface side of the glass layer.

6. The switch device according to claim 5 , wherein the support portion is a part or the whole of the switch portion.

7. The switch device according to claim 5 , wherein the support portion is disposed outside the switch portion.

8. The switch device according to claim 1 , further comprising a bonding layer interposed between the glass layer and the switch portion.

9. The switch device according to claim 1 , further comprising a resin layer interposed between the glass layer and the switch portion.

Citation Information

Patent Citations

  • Grommet

    JP1994203679A

  • Resistance film system touch panel

    JP2012059685A

  • Transmitter and fire hydrant device

    JP2020129299A

  • Glass keyboard

    US20140218640A1

  • Computer with keyboard

    US20190033923A1